Mineralogia e geoquímica da palygorskita e argilominerais associados da fácies lagunar da Formação Alcântara, Cretáceo Superior da Bacia de São Luis – Grajaú - AMORIM, Kamilla Borges (Universidade Federal do Pará, 2019)
The Alcântara Formation lithotypes (pelites, sandstones and dolomites) outcrop along the cliffs in the town of Alcântara, Maranhão state, and are characterized by the occurrence of the clay mineral palygorskite mainly in the form of whitish pockets, more specifically in pelitic levels. This unit is represented by shoreface deposits generated by storms processes, covered by lagoon/washover and tidal channel, comprinsing a progradational succession. In this paper, the results of mineralogical characterization of these rocks are presented, in order to understand/define palygorskite origin (autigenic or detrital), discuss the geochemical context of paleoenvironmental conditions of rich-magnesium clay minerals formation and theirs paragenesis, specially the relation between palygorskita and dolomite. Furthermore, this research shows a preliminary assessment of mineral potential of palygorskita occurrence, showing the levels where this mineral is massive and the approximate thickness of the packets. A geological profile was described at Baronesa Beach, where 22 samples were collected in two field stages. After laboratorial preparation, they were submitted to the following instrumental techniques: X-Ray diffraction (XRD), X-Ray fluorescence, thermal analysis (DTA-TAG) and scanning electron microscopy (SEM). The first field stage results and chemical and mineralogical analysis were utilized in the submitted and accepted paper by Cerâmica journal. These data show that Baronesa Brach profile is composed of sandstones, in the base, succeeded by mudstones with dolomites intercalations. In the mudstones, a vast clay mineral assemblage was described, characteristic of lagoonal environment, with variations in the contents of palygoskite, dolomite, chlorite, illite, smectite and traces of kaolinite and feldspars. Two different generations of palygorksite were described: (1) in the form of pockets or macroscopic accumulations in the rich-palygorskite pelitic levels, and (2) in the massive form, as the higher pelitic levels dominant mineral of the Baronesa Beach profile. The second generation, described for the first time in this paper, may constitute metric levels with potential economic interest. In the second field stage, analysis were performed with more detail in pelitic layers, and also, in dolomitic layers. In this stage, it was possible to observe that palygorskite is indeed the dominant clay mineral in pelites, and appear as trace mineral in dolomitic levels. Data reveal that palygorskite contents tend to increase in the upper portions of the profile, showing an inversely proportional relationship with chlorite and illite clay minerals, whose values decrease as palygorskite increases. The relationship between palygorskite and dolomite is also very significant, because when the first mineral is the dominant, dolomite appears as the second most abundant mineral. This relationship is accentuated when SEM data are analysed, because both minerals always occur associated. Palygorskite micromorphological analysis indicate its origin is autigenic, that is, it was formed “in situ”, since its features do not exhibit any wearing or reworking, eliminating any possibility of detrital origin. It is known that palygorskite can be found in association with carbonate rocks and that the appropriated conditions for its formation are semi-arid to arid climate, high Si and Mg activities with Al available, and alkaline pH (~8). These conditions, added to mineralogical assemblage, indicate that Mg concentration in solution was probably enough to precipitate palygorskite, after dolomite formation. Others factors, such as changes in physic-chemical conditions (Si increasing by the consumption of other minerals (chlorite and illite?)), may also have favoured palygorskite precipitation. In addition to the observed results, new XRD data showed that upper horizons of the profile, approximately 4m of pelites, are the ones with the highest palygorskite concentration. This mineral occurrence seems to be very significant, with very high contents in some horizons, revealing prospects of future works related to industry properties of this mineral, to a better quantifying and to possibilities about its economic use.